A NEEDS ANALYSIS OF VIETNAMESE USERS OF JAPANESE, KOREAN, AND CHINESE LANGUAGES - Quynh, Nguyen Thi Ngoc; Hien, Tran Thi Thu; Sao, Bui Thien; Thao, Nguyen Thi Phuong; Chi, Nguyen Thi; Hoa, Nguyen Quynh (VNU Journal of Foreign Studies, 2021)
Playing a vital role in the process of developing a test, needs analysis is often paid attention to in the first phases of planning language tests, especially large-scale ones. In the context of the project entitled “Developing Standardized Tests of Proficiency for Vietnamese Users of Japanese, Korean, and Chinese”, a needs analysis of Vietnamese users of Japanese, Korean, and Chinese was implemented. Specifically, the reported study’s goal was to investigate the activities in which Vietnamese adults frequently use their skills of Japanese, Korean, and Chinese and examine whether there were differences across activities and languages. Surveys were established with questions of frequency on particular activities either suggested by the researchers or proposed by the respondents themselves. Collected responses were analyzed using descriptive statistics and ANOVA. The results disclosed the extent to which language users utilized their language skills in different activities and the significant differences in the use frequency across different activities within each language and across languages for particular activities. The findings have served as a strong foundation and useful reference for the task design in the test development phase of the project.